Poplar Autophagy Receptor NBR1 Enhances Salt Stress Tolerance by Regulating Selective Autophagy and Antioxidant System - Su, Wanlong; Bao, Yu; Lu, Yingying; He, Fang; Wang, Shu; Wang, Dongli; Yu, Xiaoqian; Yin, Weilun; Xia, Xinli; Liu, Chao (Frontiers in Plant Science, 2021)
Salt stress is an adverse environmental factor for plant growth and development. Under salt stress, plants can activate the selective autophagy pathway to alleviate stress. However, the regulatory mechanism of selective autophagy in response to salt stress remains largely unclear. Here, we report that the selective autophagy adaptor PagNBR1（neighbor of BRCA1）is induced by salt stress in Populus. Overexpression of PagNBR1 in poplar enhanced salt stress tolerance. Compared with wild type (WT) plants, the transgenic lines exhibited higher antioxidant enzyme activity, less reactive oxygen species (ROS), and higher net photosynthesis rates under salt stress. Furthermore, co-localization and yeast two-hybrid analysis revealed that PagNBR1 was localized in the autophagosome and could interact with ATG8 (autophagy-related gene). PagNBR1 transgenic poplars formed more autophagosomes and exhibited higher expression of ATG8, resulting in less accumulation of insoluble protein and insoluble ubiquitinated protein compared to WT under salt stress. In summary, our results imply that PagNBR1 is an important selective autophagy adaptor in poplar and confers salt tolerance by accelerating antioxidant system activity and autophagy activity. Moreover, the NBR1 gene is a potential important molecular target for improving stress resistance in trees.